ANALISIS DAN PENINGKATAN KUALITAS LAYANAN PRODUSEN AMDK DENGAN MENGGUNAKAN INTEGRASI SERVQUAL DAN KANO DI CV. ALAMI BANJARMASI - Aditya Mahadwiantara; Yenny Sari; Rahman Dwi Wahyudi (CALYPTRA, 2018)
Mineral water becomes an important product for human being, This is the reason why CV. Alami runs the mineral water production company in Banjarmasin, South Kalimantan and in order to keep the customers satisfied, CV.Alami has to enhance its quality of service . Therefore, an analysis of service quality and its enchancement was needed. This research intregated Kano and SERVQUAL methods as well as 5whys method to formulate the improvement. The attributes which were needed to be improved were“employee responding the complaintwell”, “speed of complaint respon”, “usedgallon protector in shipping”, “friendly employee in when serving transaction”, “give discount”, “Give promo event”, “suitability of shipping quantity”, “easy to contact the call center of the company”, “shipping price are precise”, “Gallon packaging resistance”, “mineral water free from stink”. From the 11 service attribute, there were 10 suggestions being implemented.